Morphometric analysis of the anatomic structures adjacent to fossa lacrimal in computed tomography: Study of 100 patients - Candeias Deus, Joana (2018)
Objectives: morphometric description of anatomical structures adjacent to the lacrimal fossa and discussion of their surgical applicability.Study Design: Cross-sectional and retrospective.Methods: Computed tomography of paranasal sinuses in 100 patients.Results: Regarding the lacrimal fossa, the anterior limit of the middle turbinate head was anterior, adjacent and posterior in 45.5%, 10% and 44.5% of cases, respectively. The thickness of the ascending branch of the jaw in the area of the osteotomy was 5.2 mm. The lateral insertion of the process uncinate was pos lacrimal, lacrimal and pre lacrimal 52%, 33% and 15% of cases, respectively. The nasolacrimal duct and the lacrimal fossa measured 12.8 and 11 mm, respectively. The distance between naso lacrimal canal and the bone insertion of the middle turbinate was 4.8 mm. Approximately 60% of the lacrimal fossa is located above the middle turbinate insertion. The distance between the lacrimal fossa and the Agger Nasi was 6 mm.Conclusions: The values obtained are similar to those found in the literature. At least half of endoscopic dacryocystorhinostomy procedures (DCR En) require additional procedures. CT SPN is essential in the study of patients with indication for DCR En.